Literature : Reading fiction, poetry and drama - DiYanni, Robert (Boston McGraw-Hill, 2000)
This book offers a lively introduction to the study of fiction, poetry, and drama, and is appropriate for introduction to literature courses as well as literature-based composition courses. Known for its clear presentation of the formal elements of literary analysis, DiYanni's Literature effectively balances classical, modern, and contemporary works across the three major genres, blending well-known writers with a diverse gathering of newer, international figures.
Includes index
Keywords: Cơ bản